Reduction Coal Hauling Tonnage Losses using Weigh-In-Motion Truck Scale at PT Borneo Indobara - Setiawan, Hary; Utama, Akbar Adhi (Jurnal Syntax Transformation, 2025)
The persistence of manual weighing practices in coal transportation has led to significant revenue losses at PT Borneo Indobara, with a recorded discrepancy of -1.218% in coal tonnage reconciliation during Q4 2023—exceeding the company’s ±0.5% threshold. This research aims to identify the root cause of this issue, evaluate alternative solutions, and propose a strategic implementation plan to eliminate manual weighing. Employing the Current Reality Tree (CRT) method, the study found that the core issue was the absence of prior investigation into weighing alternatives. Using both primary (interviews, FGDs, observations) and secondary data (company reports, standards), three alternatives—Weighbridge, Low-Speed Weigh-in-Motion (LS-WIM), and High-Speed Weigh-in-Motion (HS-WIM)—were assessed using the Analytic Hierarchy Process (AHP) based on accuracy, productivity, and investment cost. The LS-WIM alternative emerged as the most optimal, scoring 0.37, due to its high productivity and moderate cost, despite slightly lower accuracy. Implementation is planned through a structured PDCA-based approach, covering proposal development, tendering, construction, and commissioning. With LS-WIM's expected accuracy of ±2%, the study projects a reversal of revenue loss into a gain of approximately USD 314,963.27, illustrating the business value of replacing manual weighing. This research contributes a novel integration of CRT and AHP methodologies in the coal logistics context and provides an actionable, stakeholder-informed roadmap for technology implementation. Future studies are encouraged to explore long-term performance, hybrid system integration, and cross-industry applicability of weigh-in-motion technologies.